ZAKAZ PROWADZENIA POJAZDÓW MECHANICZNYCH NA ZAWSZE - Zygmunt, Julia (Zeszyty Prawnicze, 2017)
A P e r m a n e n t P r o h ib it io n t o D r iv e V e h ic l e s Summary Taking into consideration present needs of security in communication, the legislator has significantly modified the regulations concerning prohibition to drive vehicles. In art. 42 § 3 and § 4 of the Penal Code (hereinafter referred to as „PC”) the prerequisites of facultative (§ 3) and obligatory (§ 4) application of this measure are defined. From the beginning of the validity of this regulation it has been a subject of discussions in the legal doctrine. As far as discussed regulation seems to be coherent with demands of everyday users of law and is fully justified by increasing traffic offence, especially connected with perpetrator’s state of insobriety, the text of some of the provisions cause many interpretative problems. This study tries to determine some of the aspects concerning facultative and obligatory grounds for adjudicating the measure. The main doubts are caused by a wide definition of the persons, who may be punished with this measure (art. 42 § 3 PC). It provides that, this measure may be applied to the „person participating in a street traffic”, but not only to a driver of a vehicle but also to a pedestrian, if on conditions described in the regulation, he would commit one of the mentioned offences. In case of a graded form of the prohibition, viz. to be applied for a lifetime, described in art. 42 § 4 PC, special severity results from its obligatory adjudication, which brought out objections connected with restricting the court’s discretion. A permanent prohibition of driving any vehicle is a very repressive sanction, especially when applied to professional drivers. It may turn out that the most severe sanction adjudicated for a traffic offence from art. 42 § 3 or § 4 PC, is connected with lasting for life stigma, because, in accordance with Polish Penal Code, a person to whom it was adjudicated, will be regarded as a man with a criminal record.